Agricultural extension for women - Durutan N. (La vulgarisation, composante du développement agricole et rural : actes du séminaire de Grenade, 1994)
Agriculture is the major source of employment for both men and women in Turkey. Although the share of labour engaged in agriculture has declined since 1950, the sector still employs almost half of the labor force. Over 45 of income in rural areas is earned directly from agriculture. Women have long had an important role in Turkish agriculture. According to the 1985 Population Census, women accounted for around half of the agricultural labor force. However, their contribution is not well recognized to the extent that society, and women themselves, perceive their work as wifely duty rather than as an economic contribution. Generally, there is no rigorous gender distinction in terms of agricultural tasks; however, considerable variation is found by region and by crop. The extension service of the Ministry of Agriculture is organized at provincial, county and village level. Extension activities are mainly carried out by the Farmers' Training and Extension Division of the Provincial Directorate of Agriculture under which subject matter specialists are responsible for transferring information on eight main areas, of which home economics is one area. The Ministry of Agriculture has recently introduced a pilot women farmers' extension program under a World Bank supported 'Agricultural Extension and Applied Research Project'. Some international agencies estimate that women account for 70-80 of household food production in Sub-Saharan Africa, 65 in Asia and 45 in Latin America and the Caribbean (FAO,1984). Since greater support for women's activities constitutes a crucial step towards increased production as well as improved equity, it is important that women's present contributions a crucial step towards increased production as well as improved equity, it is important that women's present contributions to the agricultural labor force be fully recognized (FAO, 1985). Since their importance to agricultural production is significant and critical, this need for change merits special attention and effort.
Séminaire sur la Vulgarisation, Composante du Développement Agricole et Rural, 1993/11/24-26, Grenade (Spain)